Engineering students’ lifestyle in a Malaysian Public University during the COVID-19 pandemic - Nadia Anuar,; Sofea Dayana Indra,; Dini Nurina Azhan,; Swaylin Anak Andrin,; Nurhilleny Rosly,; Nurul Syafieqah Jaafar, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Unhealthy lifestyle among university students is an apparent issue in their quality of life. The criticality of this issue is supplemented by reports that students’ lifestyle was severely impacted due to the pandemic and abrupt shift to online learning. This cross-sectional study aims to investigate the lifestyle of engineering students at a Malaysian public university. This paper also seeks to determine gender differences in students’ lifestyles. Questionnaires were distributed to respondents via Google Forms to uncover their eating habits, physical activity, and sleeping habits. Data were collected for three months from four engineering programmes. Simple random sampling was employed, and 120 responses were obtained. The findings revealed that the students have been practising a moderately unhealthy lifestyle; possess average eating habits; are physically inactive, and do not attain sufficient sleep. This study also observed no significant differences between male and female students’ eating and sleeping habits. In contrast, a significant difference was reported between male and female students’ physical activities. The results also determined a moderate correlation between eating habits and sleeping habits and also between eating habits and physical activity. The findings recommend universities implement precautionary measures such as constructing relevant courses and health programmes to raise students’ awareness of the importance of a holistic lifestyle.